Playing at monarchy : sport as metaphor in nineteenth-century France - Cropper, Corry (University of Nebraska Press, 2008)
Playing at Monarchy looks at the ways sports and games (tennis, fencing, bullfighting, chess, trictrac, hunting, and the Olympics) are metaphorically used to defend and subvert, to praise and mock both class and political power structures in nineteenth-century France. Corry Cropper examines what shaped these games of the nineteenth-century and how they appeared as allegory in French literature (in the fiction of Balzac, Mérimée, and Flaubert), and in newspapers, historical studies, and even game manuals. Throughout, he shows how the representation of play in all types of literature mirrors the most important social and political rifts in postrevolutionary France, while also serving as propaganda for competing political agendas. Though its focus is on France, Playing at Monarchy hints at the way these nineteenth-century developments inform perceptions of sport even today.